Development of a Robust QSAR Model to Predict the Affinity of N-Bridged Bicyclic Sulfonamide, Pyrazole/Sulfonamide Based Dihydroquinoline and Sulfonamide –Pyrazolopiperidine γ-secretase Inhibitors - Sharma, Suman; Sharma, Pragya; Paliwal, Sarvesh Kumar; Negar, Qumar (Current Enzyme Inhibition, 2025)
<span class=
Keywords: FFNN